The Effectiveness of the Implementation of Occupational Health and Safety (OHS) in Indonesian Medical Personnel During the COVID-19 - Firdaus, Sunny Ummul; Wiwoho, Jamal; Hidayat, Muhamad Alief (Unifikasi : Jurnal Ilmu Hukum, 2023)
This research aimed to explain the effectiveness of legal protection for medical personnel, specifically in implementing Occupational Health and Safety (OHS) during COVID-19 period. The number of cases in Indonesia certainly affected the implementation of OHS for medical personnel. The initial year of the pandemic experienced various challenges concerning the availability of medical personnel, instruments, and components crucial for supporting the implementation of OHS protocols, as well as the overall condition of COVID-19. OHS accommodation for medical personnel was listed in various laws and regulations in Indonesia. Socio-legal research methods were used to deliver a detailed investigation into the legal landscape of the laws and regulations governing the implementation of OHS. The results showed that the efficacy of the implementation and adherence to 'das Sollen' and 'das Sein' legal stipulations was considered regarding the integration of OHS in conformity with legal regulations. Therefore, there is a need for synergy among the government, hospitals, healthcare workers, and relevant parties to ensure the implementation of OHS protection for medical personnel and the potential new mutated viruses in Indonesia.